Synthesis, characterization, physical and biological properties of some cholesterol derivatives - Abdul‐Reda, Nabeel Abed; Abass, Ahmed Kadhim; Gebur, Noor Ali (European Journal of Chemistry, 2016)
A series of new cholesterol derivatives have been prepared via Mitsunobu reaction. The reaction was monitored by thin-layer chromatography (TLC) technique. All new compounds were characterized by melting points, elemental analysis, FT-IR, 1H, 13C and 2D-NMR spectroscopy. The antibacterial and antifungal activity of these derivatives was also determined. The phase transitions of the prepared derivatives were measured with the aid of differential scanning calorimetry. The textures of the mesophases have been determined with a hot stage equipped polarizing microscope, also the electrical conductivity of the solutions of these liquid crystals measured by electrical conductivity meter. The analysis showed that these prepared derivatives were liquid crystals.